In planta preliminary screening of ER glycoprotein folding quality control (ERQC) modulators - Marti, L; Lia, A; Reca, I; Roversi, P; Santino, A; Zitzmann, N (MDPI, 2018)
Small molecule modulators of the Endoplasmic Reticulum glycoprotein folding quality control (ERQC) machinery have broad-spectrum antiviral activity against a number of enveloped viruses and have the potential to rescue secretion of misfolded but active glycoproteins in rare diseases. In vivo assays of candidate inhibitors in mammals are expensive and cannot be afforded at the preliminary stages of drug development programs. The strong conservation of the ERQC machinery across eukaryotes makes transgenic plants an attractive system for low-cost, easy and fast proof-of-concept screening of candidate ERQC inhibitors. The Arabidopsis thaliana immune response is mediated by glycoproteins, the folding of which is controlled by ERQC. We have used the plant response to bacterial peptides as a means of assaying an ERQC inhibitor in vivo. We show that the treatment of the plant with the iminosugar NB-DNJ, which is a known ER α-glucosidase inhibitor in mammals, influences the immune response of the plant to the bacterial peptide elf18 but not to the flagellin-derived flg22 peptide. In the NB-DNJ-treated plant, the responses to elf18 and flg22 treatments closely follow the ones observed for the ER α-glucosidase II impaired plant, At psl5-1. We propose Arabidopsis thaliana as a promising platform for the development of low-cost proof-of-concept in vivo ERQC modulation.